2022
DOI: 10.1051/bioconf/20224402001
|View full text |Cite
|
Sign up to set email alerts
|

Impact of canopy management practices on phenolic composition and sensory profile of cv. Teran wine

Abstract: The aim of this study was to investigate the impact of early leaf removal (ELR) and cluster thinning (CT) on the phenolic composition of cv. Teran berries and wines, and the sensory profile of wines at 6 and 24 months after fermentation. Although only ELR increased the concentration of total anthocyanins in the berries as compared to the untreated control (UC), both ELR and CT had higher concentration of total anthocyanins and greater colour intensity in the resultant wines than the UC. Similar effects were ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Moreover, it has already been highlighted that excessive oxidation leads to unfavorable changes in aroma, especially the loss of fruity notes [19]. It is worth mentioning that sour cherry is considered a main descriptor of Teran wine [58], and among the wines produced, the highest intensity of this aroma was found in wines produced with the control (pigeage) treatment, followed by oxygenation and remontage, while the lowest intensity was found in the délestage treatment. In general, the intensity of astringency decreases with the aging of red wines due to the structural changes in polyphenols, while the persistence of the wine's aroma increases [59].…”
Section: Sensory Characterization Of Produced Wines By Pigeage Délest...mentioning
confidence: 95%
“…Moreover, it has already been highlighted that excessive oxidation leads to unfavorable changes in aroma, especially the loss of fruity notes [19]. It is worth mentioning that sour cherry is considered a main descriptor of Teran wine [58], and among the wines produced, the highest intensity of this aroma was found in wines produced with the control (pigeage) treatment, followed by oxygenation and remontage, while the lowest intensity was found in the délestage treatment. In general, the intensity of astringency decreases with the aging of red wines due to the structural changes in polyphenols, while the persistence of the wine's aroma increases [59].…”
Section: Sensory Characterization Of Produced Wines By Pigeage Délest...mentioning
confidence: 95%
“…16 All these compounds are critical for the sensory perception of wines, determining characteristics such as color, structure, astringency, and bitterness, as well as the aging capacity. 17 In this sense, it is important to study the sensory characteristics of wines and also their association with the chemical composition. Some studies indicated that geographical origin has a direct impact on the chemical composition and ultimately on the sensory traits of wine.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Flavanols are mainly found in the seed of berries, as polymers and oligomers known as proanthocyanidins or condensed tannins . All these compounds are critical for the sensory perception of wines, determining characteristics such as color, structure, astringency, and bitterness, as well as the aging capacity . In this sense, it is important to study the sensory characteristics of wines and also their association with the chemical composition.…”
Section: Introductionmentioning
confidence: 99%
“…These can be listed as decreased photosynthesis products to the cluster [Palliotti et al 2013], limited root growth, and decreased water efficiency. Removal of leaves during berry ripening eliminates a potential source of carbon (C) and N that may cause a reduction in sugar and nitrogen accumulation [Rossouw et al 2018], affecting berry quality [Bubola et al 2022]. Reducing the total leaf area of the vine with defoli-ation applications may weaken the grapevine growth in the following years and cause a decrease in yield.…”
mentioning
confidence: 99%